Universal health coverage and equal access in Sweden: a century-long perspective on macro-level policy - Mio Fredriksson (BMC, 2024)
Abstract Background When today's efforts to achieve universal health coverage are mainly directed towards low-income settings, it is perhaps easy to forget that countries considered to have universal, comprehensive and high-performing health systems have also undergone this journey. In this article, the aim is to provide a century-long perspective to illustrate Sweden's long and ongoing journey towards universal health coverage and equal access to healthcare. Methods The focus is on macro-level policy. A document analysis is divided into three broad eras (1919-1955; 1955-1989; 1989-) and synthesises seven points in time when policies relevant to overarching goals and regulation of universal health coverage and equal access were proposed and/or implemented. The development is analysed and concluded in relation to two egalitarian goals in the context of health: equality of access and equal treatment for equal need. Results Over the past century, macro-level policy evolved from the concept of creating access for the neediest and those reliant on wages for their survival to a mandatory insurance with equal right to healthcare for all. However, universal health coverage was not achieved until 1955, and individuals had to rely on their personal financial resources to cover the cost at the time of care utilization until the 1970s. It was not until 1983 that legislation explicitly stated that access to healthcare should be equal for the entire population (horizontal equity), while a vertical equity-principle was not added until 1997. Subsequently, ideas of free choice and privatization have gained significance. For instance, they aim to increase service access, addressing the Swedish health system's Achilles' heel in this regard. However, the principle of equal access for all is now being challenged by the emergence of private health insurance, which offers quicker access to services. Conclusions: brief summary and potential implications It can be concluded that there is no perpetual Swedish healthcare model and various dimensions of access have been the focus of policy discussion. The discussion on access barriers has shifted from financial to personal and organizational ones. Today, Sweden still ranks high in terms of affordability and equity in international comparisons: although not as well as a decade ago. Whether this marks the beginning of a new trend intertwined with a decline in Sweden's welfare 'exceptionalism', or is a temporary decline remains to be assessed in the future.